A new species of Elodophthalmus from Lower Cretaceous Lebanese amber unravels the systematic placement of Elodophthalmidae and reconciling phylogenetic conflicts within Tenebrionoidea - Cai, Chenyang; Zhao, Qian; Azar, Dany (Zootaxa, 2024)
Elodophthalmidae, represented by the sole genus Elodophthalmus Kirejtshuk & Azar, is an extinct beetle family described from Lower Cretaceous Lebanese amber. Elodophthalmidae has been hypothesized to share close affinities with the extant superfamily Scirtoidea, but their exact systematic position remains elusive. Here, we describe a new species of Elodophthalmus, Elodophthalmus maksoudae sp. nov., based on a well-preserved fossil from Early Cretaceous amber collected in Hammana/Mdeyrij, Central Lebanon, the same locality as other congeneric species. Using improved imaging technologies, we reveal detailed morphological characters of the fossil, providing critical evidence for a more robust systematic placement of Elodophthalmus. Our findings present compelling evidence supporting the placement of Elodophthalmidae within the superfamily Tenebrionoidea. Furthermore, we highlight that conflicts in the interfamilial relationships within Tenebrionoidea across various datasets can, at least partially, be mitigated by adopting the site-heterogeneous CAT-GTR+G model. We suggest that the traditional reliance on site-homogeneous models in Sanger sequencing-based studies may fail to capture the complexities of nucleotide substitution patterns. With the increasing recognition of the importance of modeling among-site compositional heterogeneity, our study points to the necessity for more rigorous model testing in the phylogenetic studies of ancient lineages such as Tenebrionoidea.